(untitled) (REMUNOM, 2026)
The theme of the relationship between interdisciplinarity and cultural diversity is important when considering the contribution that the former can offer to strengthening reflection on cultural diversity as a resistance to neoconservatism in education. To this end, we sought to understand the meaning of interdisciplinarity as presented in the BNCC (National Common Curricular Base) and in the Political Pedagogical Project (PPP) of the public basic education schools studied, and its potential in strengthening cultural diversity. The research undertaken was configured as a descriptive analytical qualitative study focused on understanding the interpretations offered by the documentary analysis, in dialogue with the reference authors. Through the analysis of the BNCC, we inferred that interdisciplinarity is evident in the document, but with a confused and somewhat vague content, highlighting the methodological perspective to the detriment of the epistemological one. The PPPs of the schools replicate the situation observed in the BNCC regarding interdisciplinarity. Similarly, the BNCC and PPPs indicate the cultural diversity to be addressed in the school curriculum, without a clear allusion to the meaning to be considered, much less to its explicit discursive-epistemological articulation within the context of interdisciplinarity.